2022
DOI: 10.20452/pamw.16311
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the relationship between serum 25-hydroxyvitamin D levels and trabecular bone score in U.S. adults

Abstract: Osteoporosis is a major clinical problem in older women and men. It affects the structure and strength of bones. Vitamin D is one of important nutrients which related to bone quantity. We aimed to evaluate the positive association between serum vitamin D levels and trabecular bone score, regardless of gender or obesity. We found that serum vitamin D levels strongly relate to bone health in not only quantity but also quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Participants with history of vitamin D supplementation surprisingly had lower TBS compared to those who did not receive vitamin D in our study, which was seemingly contradicting preceding studies which showed that vitamin D deficiency was associated with lower TBS [ 35 36 ]. Participants with history of vitamin D supplementation in our study might indeed, had lower serum 25-hydroxyvitamin D level to begin with, and therefore, had vitamin D prescribed.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants with history of vitamin D supplementation surprisingly had lower TBS compared to those who did not receive vitamin D in our study, which was seemingly contradicting preceding studies which showed that vitamin D deficiency was associated with lower TBS [ 35 36 ]. Participants with history of vitamin D supplementation in our study might indeed, had lower serum 25-hydroxyvitamin D level to begin with, and therefore, had vitamin D prescribed.…”
Section: Discussioncontrasting
confidence: 99%
“…VD was first described in 1920 [11] and interest in it has not waned since then [12,13]. The rationale for exploring its association with CVD was the discovery of VD receptors' expression throughout the circulatory system [14] including cardiomyocytes [15] and human coronary artery smooth cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Higher values of TBS indicate a better microarchitecture, whereas lower values indicate a degraded microarchitecture. In addition, TBS's prediction of fracture risk has been widely reported in cross-sectional, prospective and longitudinal studies, and has been endorsed by medical societies of bone eld (IOF, the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis, and the ISCD) 12,13 .…”
Section: Introductionmentioning
confidence: 99%